The powerful synergistic effect of spiramycin/propolis loaded chitosan/alginate nanoparticles on acute murine toxoplasmosis. - Nancy Abd-Elkader Hagras; Nermine Mogahed Fawzy Hussein Mogahed; Eman Sheta; Amira Abd-Elfattah Darwish; Mohamed Ali El-Hawary; Moaaz Tarek Hamed; Bassma Hassan Elwakil (Public Library of Science (PLoS), 2022)
The novel formula of spiramycin/propolis loaded chitosan (CS)/alginate (Alg) nanoparticles (NPs) was assessed for Toxoplasma gondii (T. gondii) treatment in comparison with the commercially available spiramycin regarding tissue penetration and blood brain barrier (BBB) passage. Swiss Albino mice were inoculated intraperitoneally by 2500 tachyzoites of the virulent T. gondii RH strain. The experimental groups were treated with oral spiramycin, propolis, CS/Alg NPs, spiramycin loaded CS/Alg NPs, propolis loaded CS/Alg NPs, and spiramycin/propolis loaded CS/Alg NPs. The results demonstrated that spiramycin/propolis loaded CS/Alg NPs exerted the longest survival time with no mortality on the sacrifice day (8th) in addition to representing the highest significant parasite percent reduction of (≥96% reduction) in liver, spleen and brain designating successful tissue penetration and BBB passage. Tachyzoites treated with spiramycin/propolis loaded CS/Alg NPs demonstrated the most disfigured rapturing organism via scanning electron microscope examination along with representing an overall remarkable improvement of the histopathological pictures of liver, spleen and brain. In conclusion, spiramycin/propolis loaded CS/Alg NPs showed the uppermost efficacy in the treatment of acute murine toxoplasmosis. The safe nature and the anti-parasitic effect of each of CS, Alg, spiramycin and propolis encourage the synergistic use of spiramycin/propolis loaded CS/Alg NPs as a potent treatment for human toxoplasmosis.